2015
DOI: 10.1002/ptr.5539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resveratrol Treatment on the Pharmacokinetics of Diclofenac in Healthy Human Volunteers

Abstract: The purpose of the present study was to assess the effect of resveratrol (RSV) treatment on the pharmacokinetics of diclofenac (DIC) in healthy human volunteers. The open-label, two period, sequential study was conducted in 12 healthy human volunteers. A single dose of RSV 500 mg was administered daily for 10 days during treatment phase. A single dose of DIC 100 mg was administered during control and after treatment phases under fasting conditions. The blood samples were collected after DIC dosing and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
3
10
0
1
Order By: Relevance
“…In this study, our results are consistent with previous studies, where an increased C max , AUC, and t 1/2 with decreased k el and CL/F were found for DIC in humans after administration of diosmin (Rajnarayana et al, ), resveratrol (Bedada, Yellu et al, ), and piperine (Bedada, Kotakonda et al, ), and the observed effects are most likely the results of inhibition of CYP2C9 enzyme. It has been reported that quercetin inhibited CYP2C9‐mediated DIC 4′‐hydroxylation in human liver microsomes (Rastogi & Jana, ; Si et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, our results are consistent with previous studies, where an increased C max , AUC, and t 1/2 with decreased k el and CL/F were found for DIC in humans after administration of diosmin (Rajnarayana et al, ), resveratrol (Bedada, Yellu et al, ), and piperine (Bedada, Kotakonda et al, ), and the observed effects are most likely the results of inhibition of CYP2C9 enzyme. It has been reported that quercetin inhibited CYP2C9‐mediated DIC 4′‐hydroxylation in human liver microsomes (Rastogi & Jana, ; Si et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…As a CYP2C9 substrate, DIC has the potential to interact with various inhibitors and inducers of CYP2C9 enzyme. Several drugs (Hynninen et al, ; Kovarik et al, ; Pedrazzoli Júnior et al, ) and herbal constituents (Bedada, Boga, & Kotakonda, ; Bedada, Yellu, & Neerati, ; Rajnarayana et al, ) altered the pharmacokinetics of DIC due to modulation of CYP2C9 enzyme in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human studies dealing with the pharmacokinetics and metabolism of resveratrol have so far been limited to small cohorts, often including fewer than 50 individuals . The majority of the studies have been conducted to test its effect in single cell lines and in animal models, normally with a deductive focus on predefined hypotheses and/or findings .…”
Section: Introductionmentioning
confidence: 99%
“…1)). (References in Table 1: Zhai et al, 2016[54]; Hyatt et al, 2016[14]; Tsang et al, 2016[49]; Rai et al, 2016[39]; Li et al, 2016[25]; Jin et al, 2016[18]; Abdel-Wahab et al, 2016[2]; Kim et al, 2016[20]; Su et al, 2016[45]; Lai et al, 2016[23]; Hu et al, 2016[13]; Monserrat Hernández-Hernández et al, 2016[32]; Natalin et al, 2016[33]; Chang et al, 2016[5]; Polley et al, 2016[37]; Bedada et al, 2016[4]; Shah et al, 2016[43]; Khazaei et al, 2016[19]; Li et al, 2016[26]; Das et al, 2015[7]; Wang et al, 2015[50]; Meng et al, 2015[31]; Tan et al, 2016[47]; Sin et al, 2015[44]; Ishikawa et al, 2015[15]; Lu and Wang, 2015[28]; Ji et al, 2015[17]; Rabassa et al, 2015[38]; Pektaş et al, 2015[35]; Jang et al, 2015[16]; Meftahi et al, 2015[30]; Dong et al, 2015[10]; Pereira et al, 2015[36]; Schroeter et al, 2015[42]; Lee et al, 2015[24]; Yaylali et al, 2015[52]; Arslan et al, 2015[3]; Trung et al, 2015[48]; Ortega and Duleba, 2015[34]; Riccioni et al, 2015[41]; Mastromarino et al, 2015[29]; Yao et al, 2015[51]; Cigremis et al, 2015[6]; Zhao et al, 2015[56]; Ge et al, 2015[12]. )…”
unclassified